Application of Quality Control Circle in Improving Early Rehabilitation Intervention Rate of Stroke Patients - Wang J; Xia L; Zheng N; Sun T; Xu H; Huang C; Yue J; Qi S (Risk Management and Healthcare Policy)
Jiayu Wang,* Linglong Xia,* Naixi Zheng, Tingting Sun, Hua Xu, Cijie Huang, Jiajia Yue, Shaohua Qi Department of Rehabilitation Medicine, Zhongshan Hospital (Xiamen), Fudan University, Xiamen, Fujian, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shaohua Qi, Department of Rehabilitation Medicine, Zhongshan Hospital (Xiamen), Fudan University, No. 668 Jinhu Road, Huli District, Xiamen, Fujian, People’s Republic of China, Email qi.shaohua@zs-hospital.sh.cnPurpose: Early rehabilitation after stroke can improve the prognosis of patients and enhance the effectiveness and quality of rehabilitation. Whether Quality Control Circle (QCC), as a quality management method, can be used to improve the early rehabilitation intervention rate of stroke patients has not been reported. This study aimed to investigate the effectiveness of QCC in increasing the early rehabilitation intervention rate of stroke patients, providing a reference program for quality improvement in rehabilitation medicine.Methods: The study was conducted based on a repeated measurement design. QCC was applied to improve the early rehabilitation intervention rate of stroke patients at Zhongshan Hospital (Xiamen), Fudan University from August to December 2023. The QCC activities were conducted following the standardized sequence of theme selection, activity planning, current situation grasping, goal setting, analysis, countermeasure formulation, countermeasure implementation and review, effect confirmation, standardization, review and improvement. The effect of the QCC was evaluated by comparing the changes in the early rehabilitation intervention rate of stroke patients before and after the QCC in 9 months.Results: The early rehabilitation intervention rate of stroke patients before QCC was (45.23 ± 12.10) %, the rate after QCC was (59.55 ± 18.17) %, and demonstrated statistically significant improvement (t=3.667, P=0.006).Conclusion: Applying the method of QCC can improve the early rehabilitation intervention rate of stroke patients, which will help to improve the quality of rehabilitation medicine.Keywords: quality control circle, stroke, early rehabilitation, medical quality improvement